2007
DOI: 10.1590/s0103-64402007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the use of die spacer on the marginal fit of copings cast in NiCr, NiCrBe and commercially pure titanium

Abstract: The goal of this study was to evaluate the effect of using die spacers on the marginal fit of NiCr (M1) and NiCrBe (M2) alloys and commercially pure titanium (cpTi) (M3) copings cast by the lost wax technique. Using a metal matrix, 45 resin added extra hard type IV stone models were obtained for the fabrication of wax patterns under the following conditions: no die spacer (A), with one die spacer layer (B) and with two die spacer layers (C), with five repetitions for each condition (alloy x die). Each die was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Thickness of the spacers in both fabrication techniques were reported to directly affect the marginal and internal adaptation of dental restorations [22]. In our study, die spacer thickness of 30 µm was set for the CAD/CAM inlays and two layers of die spacer was applied for the conventionally fabricated inlays as recommended in previous studies to achieve adequate marginal fit [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Thickness of the spacers in both fabrication techniques were reported to directly affect the marginal and internal adaptation of dental restorations [22]. In our study, die spacer thickness of 30 µm was set for the CAD/CAM inlays and two layers of die spacer was applied for the conventionally fabricated inlays as recommended in previous studies to achieve adequate marginal fit [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…With the conventional casting technique, the marginal gap was the largest when no spacer was used and dramatically decreased when multiple spacer layers (up to 70 μm) were used [67]. Many studies demonstrated that too thin of a die spacer might inversely increase the gap, likely due to the lack of cement release [68][69][70][71]. Similarly, in the case of the CEREC system, increasing the spacer setting from 10 μm to 100 μm resulted in a lower AMD [19,20,72].…”
Section: Discussionmentioning
confidence: 99%
“…Stainless steel master die was fabricated with VHF-CNC Milling Machine (VICTOR-VT PLUS 15, Dhanlaxmi Engineers, India) from a stainless steel block. The master die simulated a prepared maxillary first premolar to receive a metal-ceramic restoration with 4.5 mm height, 6° taper, and 120° chamfer[ 10 ] and consisted of a 1-mm antirotational groove positioned axio-occlusally[ 11 ] [ Figure 1 ].…”
Section: Methodsmentioning
confidence: 99%